Implementasi Layanan DNS Sinkhole sebagai Pemblokir Iklan menggunakan Arsitektur Cloud - Dicky Satriawan; Primantara Hari Trisnawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
An ad blocker extension is an ad solution that interferes while surfing in cyberspace but this extension has drawbacks, namely its limited use which is only limited to a web browser or users have to download an ad blocker separately and block ads that are limited customization. An ad blocker using DNS Sinkhole is a solution to filtering advertisements by filtering traffic on a network by checking the presence or absence of DNS queries from the ad server so that adblocker usage is not limited to every application but on every network access the user uses. Ad-blocking customization is also more flexible with the Blacklist mechanism using lists, Regex and Wildcards which expands the feature in which Regex will block ads by identifying certain patterns of any domains you want to block and also Wildcards which block the domain and its subdomains by using only names its main domain. This study uses a cloud architecture to expand access from the DNS Sinkhole and to increase security, users access the cloud network using a Virtual Private Network (VPN) mechanism so that if users want to activate an ad blocker on the network they are accessing, they only need to access it by activating VPN. As a result, users get a better internet experience with no annoying ads from a site or mobile application with a 53% reduction in total requests, 57% faster load time, and less content received by the browser with Total Transfered Resources decreased by 48%.